Conocimiento y Uso sobre métodos anticonceptivos en estudiantes de una Facultad de la UNT – semestre 2018-II - Cruz Espinola, Alexis Santiago (2021)
This research is based on determining the relationship between the level of knowledge and _x000D_ use of contraceptive methods in students of a UNT faculty - 2018-II semester. The study is framed _x000D_ within the non-experimental approach, the type of research is descriptive-transversal. The sample _x000D_ consisted of 176 students from a faculty of the UNT - semester 2018 - II enrolled in the academic _x000D_ semester 2018-II of the National University of Trujillo. For the data analysis, the Simple _x000D_ Correspondence Analysis was used, concluding that, in relation to the level of knowledge about _x000D_ contraceptive methods, 61.9% of students from the Faculty of Physical Sciences and Mathematics _x000D_ have a high level of knowledge, 29.5% a regular level and 8.5% have a deficient level of _x000D_ knowledge. Regarding the use of contraceptive methods used by students, 58% if they use _x000D_ contraceptive methods, while 42% do not use contraceptive methods; being the condom the _x000D_ contraceptive method chosen by the students with 43.2% followed by those who do not use any _x000D_ method with 37.5%. A statistically significant relationship was found between the level of _x000D_ knowledge and use of contraceptive methods in the students of the Faculty of Physical Sciences _x000D_ and Mathematics, appreciating that of the total number of students, 39.8% of students with a high _x000D_ level of knowledge do use contraceptive methods, while students who have a regular level of _x000D_ knowledge, 13.6% do not use contraceptive methods and there is a slight percentage of students _x000D_ with a low level of knowledge who use contraceptive methods, 2.3%